A review of the diet, nutrients, and supplementation potential for the outcome augmentation in surgical treatment of peripheral nerve injuries - Lepić, Sanja; Lepić, Milan; Banjanin, Nikolina; Mandić-Rajčević, Stefan; Rasulić, Lukas (Frontiers in Surgery, 2022)
Objective: Although the studies have shown beneficial effects of the diet, nutrition and supplementation as an independent treatment modality, their roles are underestimated in the treatment of peripheral nerve injuries. This is in great part due to the development of efficient nerve repair techniques, combined with physical treatment and stimulation. To achieve best possible functional recovery the diet, nutrition and supplementation should be implemented within a multidisciplinary approach. The aim of the study is to provide insight into potentially beneficial effects of diet, nutrients and supplementation, in limitation of the nerve damage and augmentation of the functional recovery after surgery in a review of human and animal studies. Methods: The data related to the diet, nutrients, and supplementation effects on the peripheral nerve injuries and their treatment was extracted from the previously published literature. Results: General balanced diet as well as obesity influence the initial nerves features prior to the injury. In the period following the injury, neuroprotective agents demonstrated beneficial effects prior to surgery, and immediately after the injury, while those potentiating nerve regeneration may be used after the surgical repair to complement the physical treatment and stimulation for improved functional recovery. Conclusions: Standardized diet, nutrition, and supplementation recommendations and protocols may be of great importance for better nerve regeneration and functional recovery as a part of the multidisciplinary approach to achieve best possible results in surgically treated patients with peripheral nerve injuries in the future.